Income Analysis of Cattle Business Integrated With Rice Farming in Semangga District, Merauke Regency, Indonesia - Adrianus, Adrianus; Mekiuw, Yosehi; Rizal, Abdul; Nurliah, Nurliah; Nursalam, Nursalam (Universitas Halu Oleo, 2022)
Integration efforts generally have the main goal of increasing the production and productivity of both cattle and rice plants. Increased production and productivity will be in line with the increase in the income of farmers and will ensure the sustainability of the agribusiness system activities. The main objective of implementing integration is to increase cattle and rice plant production. The increase in production will correspond to an increase in the income of farmers and breeders, ensuring the sustainability of the agribusiness system. The purpose of this quantitative research was to evaluate the income of the cattle business integrated with rice farming. The method used was a survey with Stratified Random Sampling technique and the location chosen was Semangga because it is one of the districts in Merauke Regency with the highest rice production where the majority of the farmers integrate cattle and rice farming businesses. In this research, the population consisted of farmers as well as breeders who work together. Primary and secondary data were employed with income analysis followed by R/C Ratio analysis. In conclusion, the cattle business integrated with rice farming has the potential to be a commercial business because it can increase farmers' income by IDR 34,434,752 within one year with an R/C of 1.90.Keywords: cattle, income, integration, rice business